Association of Aspirin Intake and Myocardial Infarction Size: - Sezavar, Seyyed Hashem; Farahani, Behzad; Gholami, Saeid; Moradi, Masoud; Zarei, Mina; Ganji, Morsaleh; Miri, Shahnaz; Khalili, Neda; Jafarian Kerman, Scott Reza (Galen Medical Journal, 2012)
Myocardial infarction (MI) is one of the most important health burdens worldwide. Aspirin as an non- Steroid Anti—inflammatory drug, has been proven to be a protective factor to decrease the incidence, however its effect of MI size is still unknown. We designed this study to compare the biomarkers after MI in patients with and without aspirin intake. 378 patients were enrolled and the results showed lower cardiac troponin T and Creatine Kinases in patients with protective dose of aspirin intake. In addition, Creatine Kinases were significantly higher in patients with no history of MI. We conclude that aspirin can reduce the size of the infraction. Also, higher enzymes can be due to higher muscle content in patient without MI history.[GMJ. 2012;1(1):35-37]